ANÁLISE DA PERCEPÇÃO DE MATURIDADE ORGANIZACIONAL EM GESTÃO POR PROCESSOS: O caso de uma holding do setor elétrico brasileiro - Araujo, Leonardo Condeixa de (2011)
The functional model has limitations regarding the coordination of work and, therefore, has proved to be restrictive to deal with current reality. By enabling to building organizations more agile, integrated and flexible, the management by processes has become a competitive advantage for contemporary organizations. The companies are structuring themselves along their organizational processes and, in this transformation, several practices of management by processes are adopted. This study aims to investigate the perception of desired maturity of management by process (in light of the strategy), which will help the company achieve its vision of future, from an analysis of the maturity in process management. The literature on the subject is reviewed, identifying the major contemporary models. Based on the theoretical model of Bruin and Rosemann, we performed a case study in a holding company of brazilian eletricity sector, seeking to identify the perceptions of employees about the current state of practices in management by processes, and the desired state (in the light of company strategy). As results, was found the desired maturity situated in the fourth stage of maturity of the theoretical model referenced, and analyzed the gap between current and desired situation, which will enable the company to achieve its future vision.